Bulky bracelet jewellery: inspired by Malaysian batik / Muhammad Hasri Abdul Azis - Abdul Azis, Muhammad Hasri (2022)
Batik is an traditional art by Malaysian that was used by to decorate house clothes and etc Batik is a hearth of Malaysian. Bulky Bracelet is a well defined bracelet which bigger in size compare to a normal standard bracelet.